2007
DOI: 10.1101/gr.6281007
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of alternative splicing in the human genome

Abstract: Alternative pre-mRNA splicing increases proteomic diversity and provides a potential mechanism underlying both phenotypic diversity and susceptibility to genetic disorders in human populations. To investigate the variation in splicing among humans on a genome-wide scale, we use a comprehensive exon-targeted microarray to examine alternative splicing in lymphoblastoid cell lines (LCLs) derived from the CEPH HapMap population. We show the identification of transcripts containing sequence verified exon skipping, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(114 citation statements)
references
References 39 publications
4
107
1
Order By: Relevance
“…OAS1 is an enzyme involved in innate antiviral response with splice variants that are known to affect susceptibility to viral infection (Bonnevie-Nielsen et al 2005) and multiple sclerosis (Fedetz et al 2006). The same splice site SNP known to associate with disease susceptibility was recently shown also to associate with splicing of OAS1 in CEPH cell lines (Kwan et al 2007), a finding that is confirmed by our analysis (Supplemental Fig. 2; P < 10 À40 ).…”
Section: Polymorphisms Influencing Ptvsupporting
confidence: 78%
See 2 more Smart Citations
“…OAS1 is an enzyme involved in innate antiviral response with splice variants that are known to affect susceptibility to viral infection (Bonnevie-Nielsen et al 2005) and multiple sclerosis (Fedetz et al 2006). The same splice site SNP known to associate with disease susceptibility was recently shown also to associate with splicing of OAS1 in CEPH cell lines (Kwan et al 2007), a finding that is confirmed by our analysis (Supplemental Fig. 2; P < 10 À40 ).…”
Section: Polymorphisms Influencing Ptvsupporting
confidence: 78%
“…A previous study using the same exon arrays on two HapMap CEPH cell lines (Kwan et al 2007) reported finding 8771 heritable probe sets at a 1% FDR. This is somewhat greater than our figure of 6536 probe sets at a 5.2% FDR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent largescale studies have suggested that a relatively high proportion of human genes show variation in expression due to allele-dependent splicing. In the few experiments approaching the last phenomenon from a transcript-based perspective, known SNPs identified as candidates for a splicing effect were tested with isoform-specific PCR (Hull et al, 2007), or chip-based methods were used to seek evidence for alternative splicing (Kwan et al, 2007;Kwan et al, 2008). Hull et al (2007) analyzed the splicing patterns of 250 exons in 22 individuals who had been previously genotyped as part of the HapMap project.…”
Section: Recent Surveys Approaching Allele-dependent Splicingmentioning
confidence: 99%
“…Transcript analysis of genotyped cell lines has discovered numerous cases of allelic splicing demonstrating that polymorphisms also disrupt splicing (11,12). These types of functional variants likely account for a similarly large fraction of the detected genetic risk for complex disease and could eventually be a target for molecular intervention.…”
mentioning
confidence: 99%